Wavelet Analysis For Sunspot Time Series - جواد لميعة باقر; عبد الله لمياء طه (Journal of Economics and Administrative Sciences, 2007)
Abstract In this research we study the wavelet characteristics for the important time series known as Sunspot, on the aim of verifying the periodogram that other researchers had reached by the spectral transform, and noticing the variation in the period length on one side and the shifting on another. A continuous wavelet analysis is done for this series and the periodogram in it is marked primarily. for more accuracy, the series is partitioned to its the approximate and the details components to five levels, filtering these components by using fixed threshold on one time and independent threshold on another, finding the noise series which represents the difference between the original series and the filtered reconstructed one which supposed to be nearly white noise. The results point that there is irregularity in period length and peaks of the wave and also that there is a clear shifting for these periods.